Pain in Community-Dwelling Older Adults with Dementia: Results from the National Health and Aging Trends Study - Hunt, Lauren J. (J Am Geriatr Soc, 2015)
OBJECTIVES: To report prevalence, correlates, and medication management of pain in community-dwelling older adults with dementia. DESIGN: Cross-sectional. SETTING: In-person interviews with self- or proxy respondents living in private residences or non-nursing home residential care settings. PARTICIPANTS: Nationally representative sample of community-dwelling Medicare beneficiaries aged 65 and older enrolled in the National Health and Aging Trends Study 2011 wave. MEASUREMENTS: Dementia status was determined using a modified previously validated algorithm. Participants were asked whether they had had bothersome and activity-limiting pain over the past month. A multivariable Poisson regression model was used to determine the relationship between bothersome pain and sociodemographic and clinical characteristics. RESULTS: Of the 7,609 participants with complete data on cognitive function, 802 had dementia (67.2% aged ≥80, 65.0% female, 67.9% white, 49.7% proxy response, 32.0% lived alone, 18.8% lived in residential care); 670 (63.5%) participants with dementia experienced bothersome pain, and 347 (43.3%) had pain that limited activities. These rates were significantly higher than in a propensity score–matched cohort without dementia (54.5% bothersome pain, P < .001, 27.2% pain that limited activity, P < .001). Proxies reported slightly higher rates of pain than self-respondents, but differences were statistically significant only for activity-limiting pain (46.6% proxy vs 40.1% self, P = .03). Correlates of bothersome pain included arthritis, heart and lung disease, less than high school education, activity of daily living disability, depressive and anxiety symptoms, and low energy. Of those reporting pain, 30.3% stated that they rarely or never took any medications for pain. CONCLUSION: Community-living older adults with dementia are at high risk of having pain. Creative interventions and programs are needed to manage pain adequately in this vulnerable population.